2004
DOI: 10.1161/01.atv.0000140061.89096.2b
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Regulate LOX-1 Expression in Vascular Smooth Muscle Cells

Abstract: Objective-Atherogenesis represents a type of chronic inflammation and involves elements of the immune response, eg, the expression of proinflammatory cytokines. In advanced atherosclerotic lesions, lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is expressed in endothelial cells, macrophages, and smooth muscle cells (SMCs). In vitro, the expression of LOX-1 is induced by inflammatory cytokines like TNF-␣ and transforming growth factor (TGF)-␤. Therefore, LOX-1 is thought to be upregulated local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 41 publications
(43 reference statements)
2
73
0
4
Order By: Relevance
“…Numerous in vitro studies have shown that oxidative as well as inflammatory stimuli increase OLR1 gene expression in macrophages, endothelial cells, and probably also in SMC 31, 32, 33, 34. In addition, different animal models have confirmed upregulation of OLR1 expression in the vasculature during inflammatory and oxidative conditions 30.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous in vitro studies have shown that oxidative as well as inflammatory stimuli increase OLR1 gene expression in macrophages, endothelial cells, and probably also in SMC 31, 32, 33, 34. In addition, different animal models have confirmed upregulation of OLR1 expression in the vasculature during inflammatory and oxidative conditions 30.…”
Section: Discussionmentioning
confidence: 98%
“…The total protein extract from cells (10-100 mg) was dissolved in 50 mM Tris-HCl, pH 6.8, 1% sodium dodecyl sulfate, 2 mM EDTA, 1% 2-mercaptoethanol, 7.5% glycerol, and denatured by heating at 100°C for 10 min. Electrophoresis was performed at 100 V for 2 h. Proteins were transferred onto the nitrocellulose membrane in NuPAGE Ò transferring buffer (Invitrogen) at 40 V for 3 h. The membranes were stained with Ponseau S (SigmaAldrich) to control equal protein load as described elsewhere (Hofnagel et al, 2004). After soaking in the blocking solution overnight at 4°C, the membrane was incubated with polyclonal anti-DNase I antibody (Rockland, Gilbertsville, PA) diluted 1:1000, polyclonal anti-CAD antibody (Abbiotec, San Diego, CA) diluted 1:500, polyclonal anti-glyceraldehyde-3-phosphate dehydrogenase (GAPDH).…”
Section: Western Blottingmentioning
confidence: 99%
“…Lectin-like low-density lipoprotein (LDL) receptor-1 (LOX-1) is an oxidized LDL (oxLDL) receptor expressed in endothelial cells 4) , smooth muscle cells 5) , cardiomyocytes 6) and monocytes 7) . The LOX-1 expression in the vascular wall is very low in its basal state and can be markedly induced by oxidative stress and inflammatory cytokines 4,5) .…”
Section: Clinical Characteristics Of the Current Smokersmentioning
confidence: 99%
“…The LOX-1 expression in the vascular wall is very low in its basal state and can be markedly induced by oxidative stress and inflammatory cytokines 4,5) . Activated LOX-1 initiates various atherogenic reactions, including the adhesion of monocytes to the endothelium and the transformation of macrophages into foam cells 7) , and it has also been suggested to be involved in destabilization and rupture of atherosclerotic plaques.…”
Section: Clinical Characteristics Of the Current Smokersmentioning
confidence: 99%